Nonpayers also matter. On Lintner’s dividend partial adjustment model estimation - Kowerski, Mieczysław (Publishing House of Wroclaw University of Economics and Business, 2024)
The dividend partial adjustment model proposed by J. Lintner (1956) is still one of the most widely used tools for analysing the dividend policy of companies. This model should be estimated only on the basis of observations in which dividend payments were recorded. This causes the sample selection to be not random and so the parameters estimator of the Lintner’s model to be inconsistent. However, the level of the payouts of the companies selected for the Lintner’s model may be affected by the decisions of dividend nonpayers not selected for this model. Some authors noted this contradiction, but there are no effective methods to solve it. In the article, to solve this problem, the Heckman (1976) sample self-selection model was proposed, which consists of two equations: the participation equation, which is a probit model of the propensity to pay dividends, and the outcome equation, which is Lintner’s partial adjustment model. This was examined using an unbalanced panel of 112 companies listed on the Warsaw Stock Exchange. The results of the estimation of the Heckman model confirm that the inclusion of information about companies not paying dividends in the Lintner’s model results in a significant reduction of the dividend target payout ratio and speed of adjustment. Estimated target dividend payout ratio and the speed adjustment for the entire market may be important information for companies’ management when developing their own dividend policies.
Argumenta Oeconomica, 2024, Nr 2 (53), s. 32-51
Keywords: Lintner’s model; Heckman’s model; dividend nonpayers; unbalanced panel; Warsaw Stock Exchange